Manajemen Proses Bisnis pada Perusahaan Industri untuk Meningkatkan Efisiensi Operasional - Abdurrozzaq Hasibuan; Alya Zia A; Farid Al Buqhori; Alif Afsal Z (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Operational efficiency is one of the key indicators in determining the success of industrial companies amid increasing competition. One of the strategies that can be implemented to improve this efficiency is through systematic and integrated business process management. This study aims to examine the role of business process management in enhancing the operational efficiency of industrial companies. This research uses the literature review method by analyzing various national journal publications from the last five years relevant to the topic. The results show that implementing effective business process management helps companies reduce waste, shorten production time, and improve product quality. The utilization of information technology, particularly ERP systems, supports the integration of business processes, allowing for more effective decision-making. However, several challenges remain, including resistance to change and limitations in human resources. Therefore, the implementation of business process management requires appropriate strategies and active participation from all organizational elements to achieve the desired efficiency. Keywords: , , , ,